KETUNTASAN HASIL BELAJAR SISWA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA MATERI PERKALIAN - Nida Jarmita; Hazami Hazami (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
This research is aiming at knowing the passing grade of students’ achievement, the activity of students and teacher in the teaching learning process of perkalian by using realistic approach. It was designed by using a classroom action research that took place at Class IV-2 MIN Tungkob, Aceh Besar. The subject chosen was 37 students. The data were collected by observation and test. The data got then analyzed by using mean score and percentage formula. From the result of three cycles of teaching, it was found that students could achieve the passing grade at 83,3% classically. Students activities also showed an ideal time which is 86,5%. Meanwhile, the teacher’s ability to manage the classroom was in the level of good (4,4).